Murottal Therapy Lowers Blood Pressure in Hypertensive Patients - Rastia Irmachatshalihah; Yunie Armiyati (Media Keperawatan Indonesia, 2019)
The incidence of hypertension always increasing every year, the incidence of hypertension increased from 25,8% to 34.1% in 2018. The Hypertension’s patients were prone to psychological problems for example stress that could raise the blood pressure. The intervention non-pharmacological for lowering blood pressure is using intervention murottal. This study aims to analyze the influence murottal’s therapy to decrease blood pressure in hypertension’s patients in the community health center Bandarharjo. The design used was quasy experiment with pre test and post test used purposive samplind and random sampling got result 20 respondents. The results of statistical tests therapy murottal have effected on the blood pressure to hypertension’s patient p value= 0,000 (α<0,05). Therapy murottal can reduce the blood pressure on then patient hypertension in the work of the comunity health center of bandarharjo. The supposed nurse can do gift treatment murottal intervention can be taught and applied to lower the blood pressure to increase nursing care.